The first hard X-ray spectral catalogue of Blazars observed by NuSTAR. Issue 3 (5th May 2022) - Middei, R; Giommi, P; Perri, M; Turriziani, S; Sahakyan, N; Chang, Y L; Leto, C; Verrecchia, F
ABSTRACT: Blazars are a peculiar class of active galactic nuclei that enlighten the sky at all wavelengths. The electromagnetic emission of these sources is jet-dominated, resulting in a spectral energy distribution (SED) that has a typical double-humped shape. X-ray photons provide a wealth of information on the physics of each source as in the X-ray band, we can observe the tail of SED first peak, the rise of the second one or the transition between the two. NuSTAR, thanks to its capability of focusing X-rays up to 79 keV provides broad-band data particularly suitable to compute SEDs in a still poorly explored part of the spectrum. In the context of the Open Universe initiative, we developed a dedicated pipeline, NuSTAR_Spectra, a shell-script that automatically downloads data from the archive, generates scientific products and carries out a complete spectral analysis. The script homogeneously extracts high level scientific products for both NuSTAR 's telescopes and the spectral characterization is performed testing two phenomenological models. The corresponding X-ray properties are derived from the data best fit, and the SEDs are also computed. The systematic processing of all blazar observations of the NuSTAR public archive allowed us to release the first hard X-ray spectroscopic catalogue of blazars ( NuBlazar ). The catalogue, updated to 2021 September 30, includes 253 observations of 126 distinct blazars, 30 of which have been multiply observed.